TQM and customer satisfaction in Malaysia’s service sector - Sit, Wen Yi; Ooi, Keng Boon; Lin, Binshan; Chong, Alain Yee Loong (Emerald Group Publishing Limited, 2009)
Purpose – The purpose of this paper is to investigate the relationship between total quality management (TQM) practices and customer satisfaction (CS) as perceived by managers’ perspectives in Malaysia’s service sector. Design/methodology/approach – The data are collected from 140 managers of Malaysia’s service firms. The structural analysis is conducted to test the hypotheses in this paper. Findings – Results reveal that leadership, customer focus, information and analysis, and human resource focus are found to have significant and positive association with CS as perceived by Malaysian service sector’s managers. Research limitations/implications – There are a few limitations for this paper. First, the time sequence of the relationships between the variables could not be determined since cross-sectional data are used. Second, this paper is confined only to service industry. Lastly, the paper is only focused on managers instead of study employees at different hierarchical levels. Practical implications – This paper serves as a valuable guideline for top management to review their TQM programs and conduct assessments on a regular basis in order to facilitate CS within their organizations. Originality/value – This paper shows the importance of TQM in contributing to CS within the service context which is not studied in many past researches. This paper only looks at TQM practices from the Malaysian service industries. As Malaysia is a developing country which is moving towards the service sector, this paper will help many organizations that are in other fast growing developing nations which are moving towards the service industry.